Analisis Perbandingan Kadar Senyawa Tanin pada Buah Kakao (Theobroma cacao L.) Muda dan Matang dengan Menggunakan Metode Spektrofotometri UV-Vis - Anita Agustina Styawan; Rita Nurjanah (JCPS (Journal of Current Pharmaceutical Sciences), 2025)
Cocoa pods (Theobroma cacao L.) contain various bioactive compounds that have significant benefits for human health. One of the main components found in cocoa pods is tannin which has antioxidant, antibacterial, and antimicrobial properties. This study aims to determine and compare the tannin content of young and mature cocoa pods using the UV-Vis spectrophotometric method. This research was conducted using an observational approach. Samples of young and mature cocoa pods were collected from cocoa plantations in Nglanggeran, Patuk, Gunung Kidul. Tannins were extracted using maceration method with 70% ethanol solvent. Quantitative analysis was performed using UV-Vis spectrophotometry at a wavelength of 750.0 nm, resulting in an absorbance value of 0.877. The standard curve for gallic acid was made with the equation y = 0.0094x + 0.0299 and the coefficient of determination (R²) of 0.998. The results showed that the average tannin content of young cocoa pods was 7.696 mg/kg, while that of ripe cocoa pods was 3.810 mg/kg. Statistical analysis using Independent T-Test showed a p-value of 0.000 (p < 0.05), indicating a significant difference in tannin content between young and mature cocoa pods. This study confirms that tannin concentration decreases as cocoa pods mature, indicating the potential of young cocoa pods as a richer source of bioactive compounds.